Urgensi Mempelajari Sosiologi Pendidikan Bagi Guru Bimbingan Konseling - Viny Syahputri; Eka Susanti; Dira Zahara Fitri; Dessy Tri Afifah; Sri Puspita Della Aryadi; Muhammad Nur Huda; Wahdaniati Bancin; Sheila Natasya Murni; Yusra Faizah (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research aims to find out how important it is to study educational sociology for guidance and counseling teachers. This type of research is descriptive research with qualitative research methods. The data collection method used is literature which refers to research that has been researched and then analyzed into a scientific work. The results of this research show that guidance and counseling teachers must also be very important in socializing, especially in the world of education, because guidance and counseling teachers must be able to collaborate with any party such as students, subject teachers, homeroom teachers, school principals and others. other purposes to coordinate the development of these students.